Attitudes Toward COVID-19 Lockdown As A Risk Predictor In Panama - Ericka Matus; Jay Molino; Lorena Matus (European Scientific Journal, ESJ, 2021)
This document describes an investigation undertaken to examine attitudes towards lockdowns through COVID-19 as a psychosocial risk predictor in Panama. We conducted the study through a cross-sectional, prospective, and correlational approach. The study was constructed containing psychometric characteristics in the form of 36 Likert scale items to collect data. The instrument was sent to 233 participants via Google form between April 17 and April 30, 2020. The participants responded fully to the questionnaire. We analyzed the data by mean comparisons, correlation, and regression. There is a significant correlation between each of the studied factors and attitudes. The results indicate that women and people over the age of 51 have a positive attitude towards lockdown. Finally, from the predictive risk model in which 99.9% of the data fit., the affective factor represents 68%, the cognitive factor 22%, and the behavioral factor 10% of predictive importance for lockdown attitudes to COVID-19.